2021
DOI: 10.1021/acs.langmuir.1c00493
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of LLPS Droplets Consisting of Poly(PR) Dipeptide Repeats and RNA on Chemically Modified Glass Surface

Abstract: The liquid−liquid phase separation (LLPS) of proteins and RNA molecules has emerged in recent years as an important physicochemical process to explain the organization of membrane-less organelles in living cells and cellular functions and even some fatal neurodegenerative diseases, such as Amyotrophic Lateral Sclerosis (ALS) due to the spontaneous condensation and growth of LLPS droplets. In general, the characterization of LLPS droplets has been performed by optical microscopy, where we need transparent subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…The diffusion of the LLPS droplets at the solid/liquid interface could be the switching between diffusion and immobilization mode. 23 To this end, we utilized the linear region of MSD with a time range of less than 0.1 s to estimate the diffusion coefficients for LLPS droplets. For a quantitative comparison between these two peptides, we derived the diffusion coefficients of LLPS droplets on the glass surfaces by fitting with eq 1 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion of the LLPS droplets at the solid/liquid interface could be the switching between diffusion and immobilization mode. 23 To this end, we utilized the linear region of MSD with a time range of less than 0.1 s to estimate the diffusion coefficients for LLPS droplets. For a quantitative comparison between these two peptides, we derived the diffusion coefficients of LLPS droplets on the glass surfaces by fitting with eq 1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“… 11 Recently, we reported that the chemically modified glass surfaces affect the diffusion of LLPS droplets and their immobilization on the glass surface. 23 This study gave us a way to control the interactions of LLPS droplets with the glass surface via the control of the net charge of the surface by the chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the surface motion behavior of LLPS droplets has been investigated on a transparent glass surface through fluorescence microscopy. [152] Two surface diffusion modes exist (fix mode and dif- Meanwhile, the distribution of charges in LLPS droplet components also affects droplets assembly (in this case, also made up of peptides and RNA) and their diffusion ability; such a process is related to motor neuronal cell death in amyotrophic lateral sclerosis (ALS) disease. [153] According to fluorescence recovery after photobleaching (FRAP) measurements reflecting diffusion efficiency, droplets of peptide variants with small charge periodicity have a faster FRAP recovery rate than that with larger periodicity, suggesting differences in internal exchange.…”
Section: Motionmentioning
confidence: 99%
“…For instance, the surface motion behavior of LLPS droplets has been investigated on a transparent glass surface through fluorescence microscopy. [ 152 ] Two surface diffusion modes exist (fix mode and diffusion mode) and the distribution of these two diffusion modes can be tuned by chemical modification of the glass surface with positive charges due to Coulomb interactions between such droplets and the solid surface. The droplets studied contained a negative ζ‐potential and consisted of peptides and RNA, but it is plausible for gel‐material‐based membraneless droplets to exhibit the same properties and, depending on their ζ‐potential (which can be tuned based on their composition) encapsulate different types of molecules.…”
Section: A Potential Material‐based Panspermia Modelmentioning
confidence: 99%
“…One such function of peptides is the assembly of membraneless coacervates through binding with primitive nucleic acids followed by phase-separation. Such membraneless coacervates have been investigated and could contribute functions such as biopolymer segregation and exchange [11], diffusion [12], growth and division [13], enhancement of compartmentalized reactions [14,15], and even scaffolding of other self-assembled structures [16][17][18] to an evolving prebiotic chemical system. Recent studies have found that more higher-order structures can assemble within peptide-DNA coacervates, leading to potential emergent functions with greater complexity depending on the environmental conditions and identity of the coacervate-forming polymers.…”
mentioning
confidence: 99%